1.1 Non-Invasive Prenatal Testing Using Cell Free Fetal DNA in Maternal Plasma: An Aid to Prenatal Sonographic Diagnosis. (26th April 2013) - Chitty, LS; Barrett, A; Mackay, F; Fielding, S; Lench, N
Abstract : Cell free fetal DNA (cffDNA) circulates in low concentration in maternal plasma and is a source of genetic material for safe non-invasive prenatal testing (NIPT). It is in routine use in the UK for fetal RHD determination in RhD- mothers, for fetal sex determination in pregnancies at risk of sex-linked disorders and for some single gene disorders. In the US and UK private sector, it is used for aneuploidy testing in high risk women. We reviewed all cases in our unit where NIPT had been requested to help with interpretation of unexpected sonographic findings and identified 16 cases (see Table ). Use of NIPT allowed us to come to a definitve diagnosis without jeopardising the pregnancy in several fetuses with skeletal anomalies, and was particularly useful in the two sets of twins* discordant for TD. Determining fetal genetic sex informed the diagnosis and/or aided counselling in five cases. Those offering sonographic diagnosis should be conversant with NIPT, particularly as the scope of this new and safer testing is increasing with technological developments and access to next generation sequencing.